Oenothera resicum (Onagraceae), a new species and the first record of the family from the Revillagigedo Archipelago, Mexico - Benavides, Eva; Kuethe, J.r.; Ortiz-Alcaraz, A.; León De La Luz, J.l. (Phytotaxa, 2019)
Oenothera resicum (Onagraceae) is here described and illustrated. This is the first record of the Onagraceae family in the Revillagigedo Archipelago, Mexican Pacific. The new species, presently known only from Isla Clarión, has characteristic features of species of subsect. Raimannia, from which can be differentiated by its perennial habit, glabrescent large fruits, glabrous sepals, conspicuously dentated leaves, stigma surrounded by the anthers at anthesis, basal rosette absent, and its particular ecological habitat. The species description, ecological information, habitat and conservation assessment are also discussed. Additionally, a key for the species of subsect. Raimannia distributed in Mexico is provided.